Closing the Equity Gap of Access to Emergency Departments of Private Hospitals in Thailand. (26th September 2018) - Suriyawongpaisal, Paibul; Atiksawedparit, Pongsakorn; Srithamrongsawad, Samrit; Thongtan, Thanita
Abstract : Background. Previous policy implementation in 2012 to incentivize private hospitals in Thailand, a country with universal health coverage, to provide free-of-charge emergency care using DRG-based payment resulted in an equity gap of access and copayment. To bridge the gap, strategic policies involving financial and legal interventions were implemented in 2017. This study aims to assess whether this new approach would be able to fill the gap. Methods. We analyzed an administrative dataset of over 20, 206 patients visiting private hospital EDs from April 2017 to October 2017 requested for the preauthorization of access to emergency care in the first 72 hours free of charge. The association between types of insurance and the approval status was explored using logistic regression equation adjusting for age, modes of access, systolic blood pressure, respiratory rate, and Glasgow coma scores. Results and Discussion. The strategic policies implementation resulted in reversing ED payer mix from the most privileged scheme, having the major share of ED visit, to the least privileged scheme. The data showed an increasing trend of ED visits to private hospitals indicates the acceptance of the financial incentive. Obvious differences in degrees of urgency between authorized and unauthorized patients suggested the role of preauthorization as a barrier to the noncritical patient visiting the ED. Furthermore, our study depicted the gender disparity between authorized and unauthorized patients which might indicate a delay in care seeking among critical female patients. Lessons learned for policymakers in low-and-middle income countries attempting to close the equity gap of access to private hospital EDs are discussed.